Visit to the Lower Kamula Youth Group and their greenhouse in Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
In May 2014 CCAFS East Africa team made a visit to some of the climate-smart village farmers in Western Kenya. These are the photos from the Youth Group visit and how they are getting on with their Greenhouse activities. Photos: C. Schubert (CCAFS)